PENGARUH SELF EFFICACY DAN HABITS OF MIND TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Nabila Ulfa, Zahra; Putri Sofia Rini; Amanda; Rosida Rakhmawati Muhammad; Bambang Sri Anggoro; Dona Dinda Pratiwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research was to examine and gather information on the following relationships between students' Critical Thinking abilities: (a) Self Efficacy; (b) Habits Of Mind; and (c) the combined effects of the two. The study employed a quantitative approach, utilizing SPSS for multiple regression and partial regression analysis. Participants in this study were eighth graders from Bandar Lampung's junior high schools. The 89 participants in this study came from two different schools in Bandar Lampung: SMPN 29 and SMPN 44. In this investigation, the instrument utilized both tests and non-tests. The study's findings indicate that students' Critical Thinking abilities are impacted by two main factors: Self Efficacy and Habits Of Mind. When taken together, these two factors account for 65.6% of students' Critical Thinking abilities, while 34.4% is explained by factors not included in the study.